Tindak Lanjut Supervisi Klinis Di SD Negeri Sabrang Lor No. 78 Surakarta - , Tukiyem, Prof. Dr. Markhamah, M.Pd, Dr. Ahmad Fathoni, M. Pd (2017)
The purpose of this research to describe the follow-up of clinical supervision at Sabrang Lor 78 Surakarta's elementary school by describing the preparation of acts of clinical supervision and efforts to overcome obstacles clinical supervision. This research uses qualitative method carried out for about 6 months, from July to December 2016. Data collected by the results of observation, interviews, and documentation. Source data from principals and teachers as informants. Data collection techniques used observation, interview and documentation. Analysis of the data in this research using the technical analysis of the data within the site. Analylisis Interactive Model of Miler and Huberman, who divides steps are in the data analysis activities with some parts of the data collection, data reduction, data presentation, and conclusion or verification Based on the discussion of research findings between lay preparation follow-up clinical supervision to do document completeness observation learning administration, conduct observations of learning, conduct observations learning evaluation findings. Implementation follow-up clinical supervision between lay principals give teachers against strengthening, training focused in component Preparation of lesson plans, training analyzes test items, and media training use learning and props.